Endogenous bioelectrical signals in development, regeneration, and neoplasm - Levin, Michael (Henry Stewart Talks, 2011)
Defining bioelectricity, Sources of bioelectrical signals, Big questions about bioelectricity, Membrane voltage and cell plasticity, History of the field of bioelectricity, Applying exogenous electric fields in vitro, Microelectrode impalement, Detection of extracellular ion flux, Investigating signals in pattern formation, Inverse pharmacological screen, Transmembrane voltage gradient characterization, Loss- and gain-of-function analyses, Synthesizing data into a predictive model, Control of cell behavior by electric fields, Mammalian stem cell differentiation, Cell orientation and outgrowth, Transepithelial potentials, electric fields, cancer, Mechanisms of electric field sensing by cells, Bioelectric signals in 3D morphogenesis, A pathway for tail regeneration, Transmembrane potential in tail regeneration, V-ATPase function in tail regeneration, Using voltage- and pH-sensitive dyes, Induction of the V-ATPase following injury, Electrogenic targets in mitosis upregulation, Axon patterning requires specific ion fluxes, Gene expression requires specific ion flows, Ion flux and induction of regeneration, Voltage gradients control large-scale axial polarity, Transmembrane potential and cell behavior, The Goldman equation, Missexpressing specific ion transporter mRNAs, Melanocyte behavior & transmembrane potential, Taking advantage of endogenous ion transport, Controlling transmembrane potential, Modulation of transmembrane potential, Controlling proliferation rates using K channels, Cell-autonomous mechanisms, Non-cell-autonomous mechanisms, Bioelectrical signals and canonical pathways, Bioelectric gradients and gene expression, Information carried by bioelectric signals, Bioelectrical mechanisms, DNA, mRNA & protein, Control of ion flux as a "master regulator", Applications in cancer, stem cells & regeneration, Light-gated ion transporters